EFEKTIVITAS MUSRENBANG DALAM PENYUSUNAN APBD KABUPATEN SUBANG - Zaenal Hirawan (Universitas Sultan Ageng Tirtayasa, 2014)
Musrenbang is one that is bottom up a forum or community participation in orderto determine the level of development. The fact this forum only legalize the interests of agroup of people who have a particular interest in determining policy. This illustrates thatMusrenbang not been consistent in determining the structure of the budget in regionaldevelopment. Additionally, Musrenbang considered less effective to reflect thatdevelopment patterns do a community needs